Efficient and flexible intelligence on the edge = Wydajne i elastyczne przetwarzanie na brzegowych węzłach bezprzewodowej sieci sensorów - Turchan, Krzysztof; Piotrowski, Krzysztof; Michta, Emil (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The paper presents a way to move away from the classical approach to data transfer in WSN systems. It aims to reduce the amount of data transmitted in the WSN by preprocessing data at edge nodes, which directly affects the occupancy of free radio frequencies such as 868 MHz.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne